(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
In this time of COVID-19, continued and relentless violence against BIPOC, organized resistance by many young people, and violent institutionalized attempts to suppress resistance, demonstrations and social change movements, what should educators be thinking about as we return to our college classrooms? In this short piece, we share our thinking and experience about our students’ psycho-social needs and our belief that faculty must be focused both on students’ and faculty’s socio-political context and students’ and faculty’s emotional wellbeing as we think about teaching and learning for this moment.